ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL GETARAN, GELOMBANG, DAN BUNYI DITINJAU DARI GAYA BELAJAR - Ningsih, Tri Ayu Widya; Rakhmawan, Aditya; Sutarja, Maria Chandra; Yamin, Yamin; Ahied, Mochammad (Natural Science Education Research, 2023)
The purpose of this research is to determine the description of students' learning styles and the percentage of student errors in relation to learning styles at SMP Negeri 3 Bangkalan on the subject of Vibrations, Waves, and Sound. This research uses a quantitative method. The population of the study consists of all students in class VIII in the academic year 2022/2023. The sampling technique used is nonprobability sampling, specifically purposive sampling. The research sample consists of 22 students. Data is collected using a learning style questionnaire and problem-solving questions related to Vibrations, Waves, and Sound. The results of the research show that: 1) The students' learning styles are categorized as visual for 9 students, auditory for 7 students, and kinesthetic for 6 students. 2) Students with a visual learning style make the most errors in their final answer, accounting for 26.43% of the errors. Students with an auditory learning style make more errors in the process and final answer, accounting for 22.83% of the errors. Students with a kinesthetic learning style make more errors in the final answer, accounting for 21.47% of the errors